Characteristics of patients admitted to the ICU with Kaposi sarcoma herpesvirus-associated diseases. (15th November 2022) - Hansen, Megan E.; Mangusan, Ralph; Lurain, Kathryn; Odeny, Thomas; George, Jomy; Lu, Crystal; Manion, Maura; Widell, Anaida; Ekwede, Irene; Whitby, Denise; Gulley, James L.; Kadri, Sameer S.; et al.
Abstract : Objective: There are four conditions caused by Kaposi sarcoma herpesvirus (KSHV): Kaposi sarcoma, KSHV-associated multicentric Castleman disease (MCD), primary effusion lymphoma (PEL), and KSHV inflammatory cytokine syndrome (KICS). These KSHV-associated disorders (KADs) often occur in people with HIV and can lead to multiorgan dysfunction requiring admission to the ICU. However, little is known about patient outcomes in this setting. Methods: A retrospective study of patients with KADs admitted to the ICU between 2010 and 2021 was conducted, examining KAD admission diagnoses, HIV characteristics, selected cytokine profiles, and ICU interventions. Primary outcomes were 60-day and median overall survival from ICU admission to death from any cause. Results: Forty-seven patients (all but one with HIV coinfection) were included. At ICU admission, 44 patients (94%) were on antiretroviral therapy with a median CD4 + count of 88 cells/μl and HIV viral load of 23 copies/ml. The most common presentation was respiratory failure alone (19%) or with hypotension (17%). Twenty-two (47%) patients had presumed KICS (with or without Kaposi sarcoma) at admission and an additional KAD was diagnosed in 36% of these patients. IL-6 levels did not vary across KAD subtype. Twenty (43%) patients received KAD-directed therapy in the ICU. Sixty-day survival was 70% and median overall survival was 9 months. Conclusion: The majority of patients with HIV and KADs admitted to the ICU had well controlled HIV. Additional KAD were diagnosed during ICU admission in a proportion of patients who presented with presumed KICS. Critical illness did not preclude a subset of patients from receiving KAD-directed therapy in the ICU.